2004
DOI: 10.1038/sj.ijo.0802586
|View full text |Cite
|
Sign up to set email alerts
|

Association between stunting and overweight among 10–15-y-old children in the North West Province of South Africa: the THUSA BANA Study

Abstract: OBJECTIVE: To investigate the relationship between stunting and overweight among 10-15-y-old children of the North West Province in South Africa. DESIGN: A single cross-sectional study design was used. The study formed part of the THUSA BANA project. SUBJECTS:The total study population of the THUSA BANA project comprised of 1257 randomly selected subjects, aged 10-15 y. MEASUREMENTS: Stunting was described as the height below the 5th percentile for age using the CDC standard percentiles. Furthermore, the defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 21 publications
(38 reference statements)
7
49
0
4
Order By: Relevance
“…1 At the same time, overweight and obesity are emerging as major problems among adults [2][3][4] and to some extent among children and adolescents in those countries experiencing the nutrition transition [4][5][6] Cross-sectional studies have shown associations between stunting and overweight, 4,6 although a lack of association has also been reported. 7 It has been suggested that childhood undernutrition predisposes individuals to gain weight later in life. 8,9 However, there are very few prospective studies in which stunted children have been followed from childhood and their later weight determined.…”
Section: Introductionmentioning
confidence: 99%
“…1 At the same time, overweight and obesity are emerging as major problems among adults [2][3][4] and to some extent among children and adolescents in those countries experiencing the nutrition transition [4][5][6] Cross-sectional studies have shown associations between stunting and overweight, 4,6 although a lack of association has also been reported. 7 It has been suggested that childhood undernutrition predisposes individuals to gain weight later in life. 8,9 However, there are very few prospective studies in which stunted children have been followed from childhood and their later weight determined.…”
Section: Introductionmentioning
confidence: 99%
“…Because the THUSA study recruited subjects from 15 years and older, and the national food consumption survey children from 1 to 9 years, the THUSABANA (THUSA and BANA for children) study 43 was planned and implemented to gather data on a random sample of children aged 9-15 years in the North West Province.…”
Section: Implementation and Follow-up Actionsmentioning
confidence: 99%
“…Studies indicate that stunting is highly prevalent in developing countries undergoing nutritional transition 1,2 . Stunting is defined as height-for-age below the 5th percentile on the Centers for Disease Control/World Health Organization (WHO) reference growth charts or a height-for-age Z-score (HAZ) of 2 2.0 standard deviation (SD) or less, and is traditionally used as an indicator of nutritional status 3,4 .…”
mentioning
confidence: 99%
“…It should be noted that reasons for any given growth impairment may be complex. The literature suggests a complex interaction of nutritional, environmental and socio-economic factors 5 , but other contributing factors include chronic or recurrent infections 2 . Stunted children tend to gain more fat than their non-stunted counterparts during the adolescent growth phase 2,6,7 , but on the other hand it is known that in addition to both nutritional habits and puberty, the individual's genetic make-up also plays a role in this phenomenon.…”
mentioning
confidence: 99%